MICROZONING OF HAZARD VULNERABLE USING MICROSEISMIC METHOD WITH HVSR (HORIZONTAL TO VERTICAL SPECTRAL RATIO) ANALYSIS IN BAYAT DISTRICT, KLATEN, INDONESIA - Yatini, Y; Kustanto Putra , Abdurrohim; Sungkowo , Ari (Indonesian Physical Review, 2023)
The Yogyakarta earthquake in 2006 caused damage in several areas, especially in the area of Klaten Regency. As a result, many infrastructures, houses, health facilities and casualties have been damaged. The research was conducted with the target of knowing the level of earth's hazard by microzoning soil vulnerability areas in the Bayat District, Klaten, Central Java. This study used the microseismic method with the HVSR (Horizontal to Vertical Spectral Ratio) analysis method. Where are the natural/dominant frequency parameters, natural amplification, and earthquake vulnerability index as measured parameters? This study aims to carry out microzonation of disaster vulnerability risks which are interpreted from the results obtained, namely amplification maps (A0), dominant frequency (f0), earthquake vulnerability (Kg), and shear wave velocity maps at a depth of 30 meters (Vs30). Data acquisition was carried out at 19 measurement points with a spacing between points having a distance of 1-2 km using a portable TDS seismograph. The acquisition results obtained varied values with A0 values 0.9 – 8.8, f0 values 1.0 – 13.8 Hz, Kg values 0.4 – 38.5, and Vs30 values 228.1 – 1635.4 m/s. From these results it can be categorized as zoning regarding the value of the level of disaster vulnerability based on the value of earthquake vulnerability (Kg) obtained to minimize damage and casualties